REPRESENTASI TOKOH DALAM KUMPULAN CERPEN SAGRA KARYA OKA RUSMINI - Wina Hendrayani Putu; Gde Artawan; I Nyoman Yasa (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2023)
This research is a qualitative descriptive study aimed at understanding the representation of character identity in the collection of short stories titled "Sagra" by Oka Rusmini. Data was collected using observation and note-taking methods, with the researcher herself as the research instrument. The data analysis involved data collection, data reduction, data presentation, and drawing conclusions.The research findings revealed the representation of character identity in two aspects (1) Caste as the determinant of identity: The caste system plays a significant role in shaping identity and is a commonly found patriarchal culture in various societies. The Sudra caste is negatively viewed by the society around the griya (traditional Balinese house). (2) Hegemony of customs and stratification in Bali. The stratification in Bali is maintained by authoritative traditions, reinforced by familial ethics. Fanaticism is also developed and created by the noble class to legitimize the hegemony that when a woman ascends in caste, she should be respected by fellow Sudras, but her status remains below those of pure Brahmin lineage.